Fuzzy Cognitive Maps and their Application in the Economic Sciences - Iwona Bąk; Katarzyna Cheba (Ekonometria)
The main purpose of the paper is an expert assessment of the relationship existing between selected indicators carried out using a relatively new tool in economic sciences: Fuzzy Cognitive Maps. The effect of its application is a graphical presentation of the relationship between the factors identified as the key ones. In the paper 23 indicators, describing four selected goals in the Strategy for Sustainable Development, 2030 Agenda were selected. It is assumed that the sustainable development goals should be related but according to the experts opinion this only applies to some indicators. This kind of relationships can be certainly identified in the case of the goals describing social and economic development, but often also economic and environmental development. However, the research results presented in the paper do not always confirm the existence of connections between individual indicators selected for the description of the goals of sustainable development. The paper tries to explain this problem.(original abstract)